OFFICE DE-CLUTTER MEDIATES THE FACTORS AFFECTING EMPLOYEE PERFORMANCE IN THE PRODUCTION AND OPERATION DIVISION - FARIS FERDIANTO NOOR; SETIA TJAHYANTI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
The aims of this study is to analyze the effect of Supervisor Support and Self Efficacy on Employee Performance, with Office De-Clutter as a mediating variable in the Production & Operation Division of PT XYZ. This study employs a quantitative research method, with sample selection using non-probability sampling through a saturated sampling technique. Data were collected using a Likert-scale questionnaire distributed to respondents via Google Forms. The population and sample in this study consisted of 79 employees of the Production & Operation Division of PT XYZ. This study used Partial Least Squares Structural Equation Modeling (PLS-SEM) via SMARTPLS 4.0 for data analysis. The findings reveal that both Supervisor Support and Self Efficacy significantly impact Employee Performance. In addition, Supervisor Support and Self Efficacy also have a significant effect on Office De-Clutter. Furthermore, Office De-Clutter has a significant effect on Employee Performance. However, Office De-Clutter does not mediate the relationship between Supervisor Support and Employee Performance, whereas Office De-Clutter mediates the relationship between Self Efficacy and Employee Performance.